Structure of different indicators for evaluating isometric leg extensors explosive forse in top level athletes - Milivoj Dopsaj (SportLogia, 2013)
The aim of this work was to establish factore structure of different indicators force-time curve for evaluating the leg extensors explosiveness regarding different sports and both genders. The research included 378 examinees divided into 8 groups based on gender and training process distinctiveness they have been subjected to. To evaluate contractile characteristics of leg extensors, standardized equipment was used and standardized “seating leg press” test. The isometric force-time characteristics of the leg extensors were evaluated using the 15 variables during unilateral (dominant and non-dominant leg) and bilateral exertions measured at 100 and 50% of the maximal force and at 100, 180 and 250 ms from the beginning of the muscle contraction. The results obtained in this study show that the measured characteristics of the leg extensors explosive force obtained in the bi and unilateral exertions, in regard to the various sports groups, have different structures as a function separate sets of factors influenced by different mechanisms than on training in various sports disciplines.